Influence of Carbon Nano- and Micron-Sized Fibers on Structure, Mechanical and Tribotechnical Properties of Polymer Composites with UHMWPE Matrix; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Panin S. V. Sergey Viktorovich; Kornienko L. A.; Aleksenko V. O. Vladislav Olegovich; Ivanova L. R.; Shilko S. V. (2016, 2016)
Title screen